Perceptions of Malaria and pattern of treatment seeking behaviour among Tharu and Pahari communities of Jhalari - Budhathoki, Chitra Bahadur; BC, R K (Journal of Nepal Health Research Council, 2009)
Background: Community understanding and practices relating to causation, transmission, prevention and treatment are the main socio-cultural factors that can influence malaria control but studies done social aspect of malaria control are limited in Nepal. Methods: Cross-sectional study was conducted in 2003 in Jhalari VDC of Kanchanpur district where both Tharus and Pahari communities coexist. Total of 184 households were included in the study through systematic random sampling procedure for household survey. Both qualitative and quantitative methods were applied for data collection. Results: Fever, headache, chills, shivering, joint pain and spasmodic fever were the most frequently mentioned symptoms of malaria. Though most people knew that mosquito bite might cause malaria fever, they had multiple notions of malaria causations such as hot weather, living near forest, season change, overwork and weakness. They were not clear how a mosquito gets infected and transmit the disease from one person to another. The results showed that people incorporated traditional and modern elements into their concepts of the diseases and treatment strategies. Home remedy with herbs and self-treatment with anti-malarial pills are rare in both communities. Use of government health facility is significantly higher in Paharis than in Tharus. Tharus initially consult their traditional healers and visit the drug retailers in the most cases and government facility in some cases. Tharus were less informed of free diagnosis and treatment of malaria at the government health facilities. Conclusion: Both Tharus and Paharis are aware of malaria fever and actively seeking medical help from available sources of treatment; however, they are poorly informed of dangerous falciparum malaria and process of the disease transmission through infected mosquitoes. Tharus have less access to the government health facility than Paharis. Thus the improved health services in terms of availability, quality and accessibility, and effective information and communication regarding diseases and services can go a long way in tackling the problem. Key words: Malaria; Fever; Knowledge; Perceptions; Treatment; Health-seeking behaviour. doi: 10.3126/jnhrc.v6i2.2189 Journal of Nepal Health Research Council 2008 Oct;6(13) Page : 84-92